A Novel Microwave‐Assisted Carbothermic Route for the Production of Copper‐Carbon Nanotube Metal Matrix Composites Directly from Copper Oxide1. Issue 5 (20th December 2012) - Vennerberg, Danny; Quirino, Rafael; Kessler, Michael R.
Abstract Cu2O was reduced to copper via a microwave‐assisted carbothermic route using multi‐walled carbon nanotubes (MWCNTs) as the carbon source. The reaction atmosphere as well as the degree of mixing of Cu2O and MWCNTs was varied, and the resulting products were characterized as a function of microwave exposure time. Irradiation of thoroughly mixed Cu2O and MWCNTs under argon for 45 s produced Cu‐MWCNT composites with high MWCNT loading and high hardness. This new approach for fabricating carbon nanotube‐reinforced metal matrix composites eliminates many of the challenges associated with traditional methods while requiring a fraction of the time and energy.